Acidophilic microorganisms enhancing geochemical dynamics in an acidic drainage system, Amarillo river in La Rioja, Argentina. (January 2021) - Bernardelli, Cecilia E.; Maza, Santiago N.; Lecomte, Karina L.; Collo, Gilda; Astini, Ricardo A.; Donati, Edgardo R.
Abstract: The Amarillo River in La Rioja, Argentina, is a natural acidic environment that is influenced by an abandoned mine. The river is characterized by extremely low pH and high concentrations of metals and metalloids. Fe(III)-bearing neoformed precipitated minerals are widespread along the hydrological basin. This work reports the presence of different species of iron-oxidizing bacteria and demonstrates that their action has a significant role in geochemical processes of the Amarillo River, mainly by catalyzing Fe 2+ oxidation and intensifying the Fe(III)-bearing mineral precipitation. Various iron oxidizers (i.e. Acidithiobacillus ferrivorans, Leptospirillum ferrooxidans, Ferrimicrobium acidophilum, Alicyclobacillus cycloheptanicus ) were detected in enrichment cultures at different temperatures. Moreover, this is the first report confirming that Acidithiobacillus ferrivorans is able to grow at 4 °C. Other acidophilic bacteria (i.e., Acidiphilium iwatensii ) and fungi (e.g., Fodinomyces uranophilus, Coniochaeta fodinicola, Acidea extrema, Penicillium sp. and Cladosporium pseudocladosporioides ) were also detected. In vitro laboratory studies recreating natural Fe(III)-bearing mineral formation showed that mineral precipitation rate was higher than 350 mg L −1 day −1 in the presence of microorganisms whereas it was about 15 mg L −1 day −1 under abiotic conditions. Jarosite was the only mineral detected in the precipitates generated by microbial action and it was also identified in the Amarillo River bed sediments. Biological Fe 2+ oxidation rates depend on temperature which range from 8 to 32 mM day −1 at 4 and 30 °C, respectively. Finally, a conceptual model recognizing the significant microbial role is proposed to gain a better understanding of the biogeochemistry dynamics of the Amarillo River. Highlights: Microbial assessment done in the Amarillo River reveals the presence of acidophilic iron oxidizers. Microbial activity influences the geochemistry dynamics of the river. An updated conceptual model was designed to allow a better understanding of the Amarillo River ecosystem.